2009
DOI: 10.2320/matertrans.m2009297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiN Nanoparticles by Explosion of Ti Wire in Nitrogen Gas

Abstract: Nano-sized Titanium nitride powders were synthesized by electrical explosion of Ti wire under nitrogen atmosphere ranging from 0.2 to 1.5 atm. Electron microscopy and X-ray diffraction studies revealed that the reaction products are cube-shaped single phase TiN nanoparticles. The lattice parameter of TiN nanoparticles increased with nitrogen pressure in the chamber. The nitrogen content of nanoparticles was estimated from their lattice parameter being comparable to the stoichiometric composition of TiN. Small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…The measured lattice spacings of faceted precipitates are very close to that of the well-known TiN crystal structure [10], whereas the cubic shaped precipitates showed a slightly larger lattice parameter. These differences may be caused by different N contents [11]. The Ti(N) precipitates were found in random orientations and had no preferred orientation relationship with the surrounding ferrite matrix.…”
Section: Tem Analysismentioning
confidence: 98%
“…The measured lattice spacings of faceted precipitates are very close to that of the well-known TiN crystal structure [10], whereas the cubic shaped precipitates showed a slightly larger lattice parameter. These differences may be caused by different N contents [11]. The Ti(N) precipitates were found in random orientations and had no preferred orientation relationship with the surrounding ferrite matrix.…”
Section: Tem Analysismentioning
confidence: 98%
“…29) We also conducted explosion experiments in Ar gas using the Cr-coated Ti wire which is the same as the one used in this study. 28) We produced -Ti and TiCr 2 nanoparticles which are the equilibrium phases of Ti-Cr alloy of the corresponding composition.…”
Section: Resultsmentioning
confidence: 99%
“…24) We have been demonstrated that electrical wire explosion (EWE) would be a plausible method to synthesize various alloys and intermetallic nanoparticles [25][26][27][28] and also nitride. 29) In this study, we elaborated further to synthesize (Ti,Cr)N nanoparticles by this method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have successfully synthesized nanoparticles of alloys, intermetallics and nitrides by the electrical wire explosion (EWE) process. [7][8][9][10][11] In our previous work, we produced the mixture of -Ti and TiCr 2 particles along with meta-stable Ti-rich phase by exploding a Cr-coated Ti wire in argon. 10) Later on, we produced the mixture of TiN, Cr 2 N, and a few nanometer-sized fine particles, which are presumably (Ti,Cr)N, by exploding a Cr-coated Ti wire in nitrogen.…”
Section: Introductionmentioning
confidence: 99%